Oxidative dehydrogenation of ethyl benzene to styrene over hydrotalcite derived cerium containing mixed metal oxides - Venugopal, Ashok Kumar; Venugopalan, Aswathy Thareparambil; Kaliyappan, Periyasamy; Raja, Thirumalaiswamy (Green Chemistry, 2013)
Cerium containing mixed oxides derived from hydrotalcites was prepared and its catalytic activity was studied for oxidative dehydrogenation of ethyl benzene to styrene. Structural, spectroscopic and morphological features of the catalyst have been thoroughly examined with various physico-chemical characterization methods. Raman spectroscopy studies show evidence for oxygen vacancies in lower loadings of cerium which enhanced the oxygen migration. The transmission electron microscopy image showed good dispersion of ceria clusters on the mixed metal oxide. The catalytic activity results suggested that the conversion of ethyl benzene and styrene yield is stable for at least 12 hours without any significant catalyst deactivation. The styrene selectivity and ethyl benzene conversion were higher in a catalyst containing 0.03 mole percentage of cerium. Structural features of the spent catalysts have also been examined to demonstrate the stability of the catalyst during the reaction.

Renewable fuels from biomass-derived compounds: Ru-containing hydrotalcites as catalysts for conversion of HMF to 2,5-dimethylfuran - Nagpure, Atul S.; Venugopal, Ashok Kumar; Lucas, Nishita; Manikandan, Marimuthu; Thirumalaiswamy, Raja; Chilukuri, Satyanarayana V. (Catalysis Science & Technology, 2015)
Production of transportation fuels from renewable biomass is hugely important considering the current ecological concerns over CO2 built up in the atmosphere. Ruthenium-containing hydrotalcite (HT) catalysts were applied for the selective hydrogenolysis of biomass-derived 5-hydroxymethylfurfural (HMF) to 2,5-dimethylfuran (DMF). Structural and morphological features of the catalysts were examined using various physico-chemical characterization techniques. The influence of various reaction parameters, such as reaction temperature, solvent, Ru content of the catalyst, etc., was investigated with respect to HMF conversion and DMF yield. The study clearly shows that well-dispersed Ru nanoparticles are highly active and selective in the conversion of HMF to DMF. A catalyst containing only 0.56 wt% Ru converted 100 mol% HMF to yield 58 mol% DMF. This catalyst was found to be recyclable as the activity was retained even after five cycles of reaction. 2-Propanol was found to be a good solvent as it helped to improve DMF yield through transfer hydrogenation. Based on the results of the investigations, a reaction pathway for the conversion of HMF to DMF was proposed for the present Ru-based catalyst system.

Effective and selective oxidation of 2-butanol over Mn supported catalyst systems - Prabu, Kandasamy; Prabu, Marimuthu; Venugopal, Ashok Kumar; Venugopalan, Aswathy Thareparambil; Sandilya, W. V. Y. Sai; Gopinath, Chinnakonda S.; Raja, Thirumalaiswamy (Applied Catalysis A-General, 2016)
Oxidation of alcohols to their corresponding aldehydes/ketones is an important reaction in industries as well as in academic perspective. Selective oxidation (Selox) of alcohols like methanol, ethanol and propanol are well studied in literature; however, alcohols like butanol, pentanol, octanol is a challenging task. Selective oxidation of 2-butanol to methyl ethyl ketone (MEK) is an important reaction due to its wide range of applications. Herein, we demonstrated the selective oxidation of 2-butanol to MEK over Mn supported on different oxide supports. A series of MnxOy-Al2O3 (MA), MnxOy-CeO2 (MC), MnxOy-ZrO2 (MZ) and MnxOy-SiO2 (MS) catalysts were prepared by co-precipitation followed by hydrothermal method. As synthesised catalysts were characterised by various physico-chemical characterisation techniques. It was found that the presence of Mn3O4 species in MA and MZ catalysts is responsible for maximum catalytic activity towards 2-butanol oxidation. MA catalyst conferred a maximum 2-butanol conversion of 51% and 88% selectivity towards MEK. XPS analysis revealed that Mn in MA catalyst exists in +2 and +3 oxidation states and responsible for 2-butanol oxidation. Moreover it was found that the acidity of the catalyst also plays an important role in catalytic activity. (C) 2016 Published by Elsevier B.V.

Promotional effect of Fe on the performance of supported Cu catalyst for ambient pressure hydrogenation of furfural - Manikandan, Marimuthu; Venugopal, Ashok Kumar; Nagpure, Atul S.; Chilukuri, Satyanarayana V.; Raja, Thirumalaiswamy (RSC Advances, 2016)
A noble-metal free FeCu based bimetallic catalyst system prepared by facile co-impregnation method was found to be highly admirable for vapour phase selective hydrogenation of furfural to furfuryl alcohol at ambient pressure. Monometallic Cu/gamma-Al2O3, Fe/gamma-Al2O3 and bimetallic FeCu/gamma-Al2O3 catalysts with different Fe loadings were prepared. Structural and morphological features of the catalysts were thoroughly investigated by several physico-chemical characterization techniques. The influence of various reaction parameters, such as Fe loading, reaction temperature and flow of reactants was examined with respect to furfural conversion and furfuryl alcohol yield. The results clearly showed that an optimum amount of Fe is necessary to enhance the catalytic activity of monometallic Cu/gamma-Al2O3 for the selective hydrogenation of furfural. The catalyst FC-10 with 10 wt% Fe exhibited excellent activity which led to high furfural conversion (>93%) and furfuryl alcohol selectivity (>98%) under mild reaction conditions. The higher activity of bimetallic FeCu/gamma-Al2O3 compared to monometallic Cu/gamma-Al2O3 is ascribed to the formation of FeCu bimetallic particles and the existence of oxygen vacancies in the Fe oxide system. The superior activity after Fe loading on the Cu-based catalyst was attributed to the synergy between Cu and Fe. A plausible mechanism is proposed to explain the promoting effect of Fe, which involves synergism between Fe sites with strong oxophilic nature and Cu sites with a high ability for hydrogen activation. Based on the activity results, prolonged catalytic activity and spent catalyst analysis, the developed FeCu/gamma-Al2O3 catalyst is inexpensive, eco-benign and robust, which makes it a promising candidate for the efficient conversion of biomass-derived substrates to fine chemicals and drop-in biofuels.

Role of surface synergistic effect on the performance of Ni-based hydrotalcite catalyst for highly efficient hydrogenation of furfural - Manikandan, Marimuthu; Venugopal, Ashok Kumar; Prabu, Kandasamy; Jha, Ratnesh Kumar; Thirumalaiswamy, Raja (Journal of Molecular Catalysis A-Chemical, 2016)
The selective vapor phase hydrogenation of furfural at ambient pressure has been investigated using a facile and robust hydrotalcite derived Ni containing mixed oxide catalyst. The systematic characterization results conferred that the difficulty in the reduction of Ni species due to the strong interaction between Ni and support, which facilitated from the homogeneous distribution of hydrotalcite structure. It was also found that the structure and catalytic performance of the catalysts were greatly influenced by Ni loading. Through fine-tuned surface elemental sites and reaction conditions, furfural conversion of 98% with 95% of furfuryl alcohol selectivity was achieved over a MAN-2 catalyst containing two molar ratio of Ni. The results have demonstrated that the incorporation of Mg significantly enhances the Ni-support interaction, Ni dispersion and catalytic performance. The high efficiency of the Ni-based hydrotalcite derived catalyst was mainly attributed to the surface synergistic interaction between the catalytically active metallic Ni sites and the strong basic sites, which furnished an eco-benign and sustainable catalyst for the selective hydrogenation of furfural. Furthermore, the spent catalyst analysis substantiated that no significant difference in the catalyst phase was observed even after 48 h of reaction stream. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: alcohol-hydrotalcites-selective; Biomass-frurfural-furfuryl; Hydrogenation